INFLUENCE INFLATION, LEVEL UNEMPLOYMENT OPEN AND HEALTH AGAINST EXTREME POVERTY IN INDONESIA FROM AN ISLAMIC ECONOMIC PERSPECTIVE 2000-2024 USING A VECTOR ERRORS CORRECTION MODEL APPROACH - Alfin Ahmad Riyadi; A. Zuliansyah; Zulaikah Zulaikah (JURNAL PROFIT, 2025)
This study aims to analyze the influence of inflation, unemployment, and adequate sanitation on extreme poverty in Indonesia from an Islamic economic perspective. Using time series data from 2000–2024 and a Vector Error Correction Model (VECM) approach, this study examines the long-term and short-term relationships between variables. The analysis shows that inflation, unemployment, and health significantly influence extreme poverty in the long term. This means that economic factors and the quality of the community's living environment play a significant role in determining the level of extreme poverty in Indonesia. However, in the short term, only the open unemployment rate variable significantly influences extreme poverty, while inflation and health have not shown any significant impact. From an Islamic economic perspective, the results of this study emphasize the importance of implementing the principles of justice and balance in economic management, such as suppressing inflation, expanding employment opportunities, and increasing access to healthcare as an effort to reduce extreme poverty and achieve equitable prosperity in Indonesia.